Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar - Nadia Nur Afifah, Neng Ana; Aisyah, Iis; Sadiah, Ati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
The aim of this research was to determine the influence of the Problem Based Learning learning model on learning outcomes. The research method used was quasi-experimental with the research design being a non-equivalent control group design using pretest and posttest student learning outcomes on employment material. The population used was all class XI students at SMA Negeri 10 Tasikmalaya, totaling 427 students. The sampling technique used was purposive sampling which had chosen class X-12 as the experimental class and class XI-9 as the control class, with each sample class totaling 36 students. The data collection technique is a multiple choice test with 30 questions according to Bloom's taxonomy indicators from C1-C6. The data analysis technique is carried out by testing prerequisite analysis and hypothesis testing. The results of this research show that there are differences in student learning outcomes between the experimental class and the control class as seen from the posttest score in the experimental class of 82.38 and the N-gain value of 0.66. Based on the hypothesis test calculation, it can be seen that the Sig. (2-tailed) namely 0.000 < 0.05 so it can be concluded that there is an influence of the Problem Based Learning learning model on student learning outcomes